2022
DOI: 10.1038/s41467-022-34355-w
|View full text |Cite
|
Sign up to set email alerts
|

Global and regional ecological boundaries explain abrupt spatial discontinuities in avian frugivory interactions

Abstract: Species interactions can propagate disturbances across space via direct and indirect effects, potentially connecting species at a global scale. However, ecological and biogeographic boundaries may mitigate this spread by demarcating the limits of ecological networks. We tested whether large-scale ecological boundaries (ecoregions and biomes) and human disturbance gradients increase dissimilarity among plant-frugivore networks, while accounting for background spatial and elevational gradients and differences in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 65 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…There are inherent limitations in these regional SI models that generalize forest growth across ecoregion extents. While the boundaries likely do not impose undue error on our methods, as plant vegetation adheres to sharp polygon boundaries, thus supporting ecoregionalization as a useful technique for summarizing vegetation properties (Smith et al 2018, Martins et al 2022, there remains a significant loss of understanding of vegetation patterns on the landscape. Still, the results capture growth dynamics within areas of similar biogeography and climate, and reproduce a gradient of growth that is consistent with widely recognized forest structure and environmental gradients in the North American boreal domain (Brandt 2009).…”
Section: Limitations Of Regional Si Estimates From Archives Of Airbor...mentioning
confidence: 82%
See 1 more Smart Citation
“…There are inherent limitations in these regional SI models that generalize forest growth across ecoregion extents. While the boundaries likely do not impose undue error on our methods, as plant vegetation adheres to sharp polygon boundaries, thus supporting ecoregionalization as a useful technique for summarizing vegetation properties (Smith et al 2018, Martins et al 2022, there remains a significant loss of understanding of vegetation patterns on the landscape. Still, the results capture growth dynamics within areas of similar biogeography and climate, and reproduce a gradient of growth that is consistent with widely recognized forest structure and environmental gradients in the North American boreal domain (Brandt 2009).…”
Section: Limitations Of Regional Si Estimates From Archives Of Airbor...mentioning
confidence: 82%
“…The boundaries used for the ecoregion designations come from a widely used ecoregion product (Olson et al 2001). Studies show that plant vegetation adheres to sharp polygon boundaries, demonstrating the utility of ecoregionalization for summarizing vegetation properties (Smith et al 2018, Martins et al 2022. Many studies use a similar ecoregion approach for environmental stratification of LiDAR data (Bolton et al 2013, Neigh et al 2013, Hansen et al 2014, Margolis et al 2015.…”
Section: Study Areamentioning
confidence: 99%
“…The Neotropical region accounts for about half of our compiled networks, and continental areas are better covered than islands or coastal areas. It also known that species within the same biogeographical region tend to interact more and that strong species turnover between seed-dispersal networks occurs between biogeographical regions (Martins et al, 2022). Moreover, within the same biogeographical region, birds with medium to large body size or flexible diets tend to have greater range sizes due to the ability of crossing potential dispersal barriers (Claramunt et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…', the answer to which would dictate the spatial span to embed/predict. Recent results by Martins et al (2022)…”
Section: Box 2 Minding Legacies Shaping Ecological Datasetsmentioning
confidence: 99%
“…In fact, we do not have a satisfying answer to the question of ‘where does an ecological network stop?’, the answer to which would dictate the spatial span to embed/predict. Recent results by Martins et al (2022) suggested that networks are shaped within eco‐regions, with abrupt structural transitions from an eco‐region to the next. Should this trend hold generally, this would provide an ecologically relevant scale at which metawebs can be downscaled and predicted.…”
Section: The Metaweb Merges Ecological Hypotheses and Practicesmentioning
confidence: 99%